GENDER ROLE ALLOCATION IN SELECTED COFFEE POSTHARVEST ACTIVITIES - Hadiyanto, Handoko (Universitas Muhammdaiyah Surakarta, 2013)
This study analyzed the gender role allocation of wholesale-traders and coffee producers in their post harvest activities in Rejanglebong and Lebong District. It examined the major participants in the coffee postharvest subsystem, identified roles and characteristics, and their problems and needs in performing these roles. These were analyzed using descriptive statistics like frequency, percentage, mean, ranking and standard deviation. Twenty-five wholesale-traders and forty-three coffee producers served as respondents of this study. Coffee business is the major income source of the respondents. Decisions in carrying out postharvest activities were done solely by the males or jointly by males and females since males played the managerâs role. Problems encountered in performing coffee postharvest activities were: technical know-how in coffee processing; low and fluctuating prices; lack of storage facilities; occurrence of bad weather condition and too high coffee trees and difficulty in hiring laborers during peak season.